International Scientific Conference “Complex Geophysical Monitoring in Georgia: History, Modern Problems, Promoting Sustainable Development of the Country” - Varamashvili, Nodar D.; Pipia, Mikheil G. (Journals of Georgian Geophysical Society, 2024)
Information about the international scientific conference “Complex Geophysical Monitoring in Georgia: History, Modern Problems, Promoting Sustainable Development of the Country” Dedicated to 180 Anniversary of the Organization in Georgia of Regular Magneto-Meteorological Observations , which was held on October 17-19, 2024 at Ivane Javakhishvili Tbilisi State University is presented.